Effects of cascade information sharing in inventory and service level in multi-echelon supply chains. (2nd June 2009) - Chan, F.T.S.; Chan, H.K.
Information sharing has been regarded as an effective remedy to counteract supply chain dynamics, especially in the current era with advanced information technology. While sharing inventory information among supply chain members would certainly help to improve a supply chain's performance, the scale of full information sharing is rather complex because the scope of such integration is quite wide. This is because most of the supply chain members are probably located in different countries as outsourcing is now not uncommon. In this paper, a cascade information sharing approach is proposed in multi-echelon supply chains in contrast to full information sharing. The principle behind the proposed approach is to allow information sharing only to a member's immediate upstream member on its inventory information. Simulation is employed to test the effectiveness of the proposed approach and results indicate that the proposed approach is still able to minimise the problem of supply chain dynamics. The achievement is even close to the full information sharing approach subject to various service levels.